Tiếp cận nghiên cứu Hoa Kỳ học - một số vấn đề đặt ra - Ninh, Vũ Dương (VNU Journal of Science: Social Sciences and Humanities, 2004)
This is the introductory report of the conference "Approach to American study and experience learnt for Vietnam" conducted at the College of Social science and humanities on November 2003. With historical evidences, the paper states that the first Vietnamese lecturer on American history was Nguyen Ai Quoc - Ho Chi Minh at a training class of the revolutionist youth organization in 1925. His lectures were printed in the Book entitled "Revolutionary Road" in 1927. After having summarized the curriculum on American history in the Vietnamese universities since 1956, the author gives some ideas on the establishment of American study in Vietnam as follows: 1. Establishing "Program on American study” at the international Studies Faculty, College of social science, humanities. 2. Training teachers on American studies. This is of the first fundament and necessity so as to establish a human resource for studying American history in Vietnam. Simultaneously, it is necessary to set up a Room for American study containing newspapers, materials and media relating to American study. 3. Promoting exchanges among students of the two countries so that young generation has more favorable conditions to understand each other and subsequently understand aspects of each country. Hence, though relatively late, the establishment of the American study in Vietnam is necessary ancl practical to not only provide basic and systematic knowledge on a scientific field but also contribute efficiently to promotion of the relation between the two countries.